Challenges in integrating health and social care: the Better Care Fund in England. Issue 2 (April 2020) - Harlock, Jenny; Caiels, James; Marczak, Joanna; Peters, Michele; Fitzpatrick, Raymond; Wistow, Gerald; Forder, Julien; Jones, Karen
Objectives: The Better Care Fund is the first and only national policy in England that has legally mandated the use of pooled budgets to support local health and social care systems to provide better integrated care. Methods: We report qualitative findings from the first national multi-method evaluation of the Better Care Fund, focusing on its implementation, perceptions of progress and expected impacts among key stakeholders. Interviews were carried out with 40 staff responsible for Better Care Fund implementation in 16 local health and social care sites between 2017 and 2018. Results: Study participants reported their experiences of implementation, and we present these in relation to three themes: organizational issues, relational issues and wider contextual issues. Participants stressed the practical and political challenges of managing pooled budgets and the complexity of working across geographical boundaries. In a context of unprecedented austerity, shared vision and strong leadership were even more vital to achieve collaborative outcomes. Conclusion: Pooling budgets through the Better Care Fund can lever closer collaboration between sectors and services. Shared vision and leadership are essential to develop and foster this closer collaboration. Although some successes were reported, the study highlights that there are major cultural, operational and territorial barriers to overcome.